Matched Unrelated Hematopoietic Stem Cell Transplant in Juvenile-Onset Krabbe's Disease - Ruchira Misra; Sunil Bhat; Suhani Shah; Anaita Hegde; Hiren Panwala; Divyata Hingwala (Wolters Kluwer Medknow Publications, 2022)
Background: Krabbe's disease is a neurodegenerative condition caused by a deficiency of a lysosomal enzyme, galactocerebrosidase (GALC), found mainly in the brain. There are four variants based on the age of onset: Infantile, late infantile, juvenile, and adult. Hematopoietic stem cell transplants can be curative as the GALC-positive donor cells migrate to the brain and provide GALC, thus correcting the deficiency. However, this is most effective when performed in the asymptomatic or mildly symptomatic phase. Maximum experience is in infantile-onset disease. The types of transplants usually used are matched sibling donor transplant or umbilical cord blood transplant. Clinical Description: A 5-year-old girl, the only child of a nonconsanguineous marriage, presented with complaints of frequent falls and progressive visual deterioration for 2 months. After evaluation, the clinical phenotype was ascertained to be that of a juvenile-onset (>5 years) neurodegenerative disorder with neuro-axis involvement of the brain (predominantly, white motor involvement-because of gait abnormalities and visual involvement) and absence of organomegaly or any other systemic involvement. Krabbe's disease was suspected. Supportive evidence was found on neuroimaging and confirmed by a homozygous mutation in the GALC gene that was consistent with Krabbe's disease. Management: The patient was treated with a matched unrelated bone marrow transplant, a modality that is generally not used in the management of Krabbe's disease. The clinical, neurophysiological, and neuroradiological profiles are compared during a 2-year follow-up. Currently, 2 years' posttransplant, she has not deteriorated further neurologically, and though legally blind is attending a special school for the visually impaired and performing most activities of daily living independently. Conclusion: Early matched unrelated donor transplant can be beneficial in juvenile-onset Krabbe's disease.